Akhlak Menuntut Ilmu Menurut Hadis serta Pengaruh Zaman terhadap Akhlak Para Peserta Didik - Muhamad Yoga Firdaus; Susanti Vera; Muhamad Fauzi (Jurnal Riset Agama, 2021)
This study aims to discuss the concept of morality in studying according to the hadith and the influence of the times on the morality of the students. This research uses an approach method through literature study and content analysis. The results and discussion in this study include general views of morality in studying, hadith about morality in studying, and morality in studying in changing times. This study concludes that in demanding something that should not be forgotten and discussed is morality in seeking knowledge, both to the teacher, and morality to the knowledge that will be studied alone. This research is expected to provide benefits and add insight into the treasures of Islamic knowledge for readers.